Collected fragments - Gabriel, Katie, author; Osborne, Erika, advisor; Sullivan, Patrice, committee member; Lundberg, Tom, committee member; Harvey, Ashley, committee member (Colorado State University. Libraries, 2017)
This paper explores the connections between memory and identity existing in my artworks that reimagine family photographs. I am interested in the ability of photographs, objects, and patterns to prop up, and in many cases, form our understanding of past moments that connect family members who are both absent and present. My work explores how these connections forge a family's collective memory. As photos within an album create a disjointed narrative with reoccurring actors, my work questions how in time our understanding of a person, or group of people, may change. Hierarchy among the various elements captured in a photograph becomes dependent upon my emotional and aesthetic response, allowing objects or patterns to act as visceral representations of a person, and at times catalysts for masking and presenting.